Reliability of the agar based method to assess the production of degradative enzymes in clinical isolates of Candida albicans - Arantes, Paula Tamiaõ [UNESP]; Sanitá, Paula Volpato [UNESP]; Santezi, Carolina [UNESP]; Barbeiro, Camila De Oliveira [UNESP]; Reina, Bárbara Donadon [UNESP]; Vergani, Carlos Eduardo [UNESP]; Dovigo, Lívia Nordi [UNESP] (Oxford University Press (OUP), 2016)
The aim of this study was to establish a reproducible protocol using the methodology of hyaline zones around the colonies on specific agar plates for phospholipase and proteinase production. This was an in vitro double-blind experiment, in which the dependent variables were the enzymatic activity measurements (Pz) for the production of phospholipase (Pz-ph) and the production of secreted aspartyl proteinases (Pz-sap). Three independent variables give rise to different measurement protocols. All measurements were carried out at two different moments by four examiners (E1, E2, E3, and E4). The minimum sample size was 30 Candida albicans clinical isolates. Specific agar plates for phospholipase and SAPs production were prepared according the literature. The intra-and inter-examiner reproducibility for each protocol was estimated using the Intraclass Correlation Coefficient (ICC) and its confidence interval (95% CI). Based on the results obtained for both phospholipase and SAPs, there appears to be no consensus on the protocol chosen for each particular examiner. Measuring the colonies in triplicate may be the main factor associated with the increase in measurement accuracy and should therefore take precedence over measuring only one colony. When only one examiner is responsible for taking measurements, a standard protocol should be put in place and the statistical calibration of this researcher should be done prior to data collection. However, if two or more researchers are involved in the assessment of agar plates, our results suggest that the protocols using software to undertake plate reading is preferred.
Keywords: Candida albicans; Reproducibility of Results; Virulence factors